2012
DOI: 10.1021/jp307434g
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Surface and Bulk Oxides on Pd(111) Revisited by in Situ X-ray Diffraction

Abstract: We investigated the structure and formation of surface and bulk oxide on Pd(111) as a function of temperature and oxygen pressure from ultrahigh vacuum up to atmospheric pressures by means of in situ X-ray diffraction. Our X-ray diffraction data of the quasi 2-D surface oxide layer are compatible with the structural model of a Pd 5 O 4 layer proposed by density functional theory. In the temperature range from 650 to 950 K, the formation of the Pd 5 O 4 surface oxide layer can be described by a constant oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…22 Furthermore, an epitaxial PdO growing with the [101] crystallographic direction perpendicular to the surface of the substrate has also been reported for Pd(111) 8,26 although it was observed that PdO(001) may coexist with PdO(101) by SXRD. 11 The crystallographic orientation is of interest because of the presence of the oxygen undercoordinated Pd atoms on the PdO(101) surface, which The Journal of Physical Chemistry C Article have been assigned to be the sites responsible for catalytic activity. 6,21,27,28 In an attempt to analyze the diffraction pattern further, we calculated the positions of the Bragg reflections for three different epitaxial growth directions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…22 Furthermore, an epitaxial PdO growing with the [101] crystallographic direction perpendicular to the surface of the substrate has also been reported for Pd(111) 8,26 although it was observed that PdO(001) may coexist with PdO(101) by SXRD. 11 The crystallographic orientation is of interest because of the presence of the oxygen undercoordinated Pd atoms on the PdO(101) surface, which The Journal of Physical Chemistry C Article have been assigned to be the sites responsible for catalytic activity. 6,21,27,28 In an attempt to analyze the diffraction pattern further, we calculated the positions of the Bragg reflections for three different epitaxial growth directions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The binding energies of the above-mentioned surface structures are calculated with eq 5 as summarized in Table 2 Table 2. Experimentally, it is found that the phase boundary can be well-described by a line of constant chemical potential of μ O = −1.24 eV above 650 K. 19 The value of μ O determined from our DFT calculations for the transition between the oxygen p(2×2) chemisorption phase and the Pd 5 O 4 surface oxide phase is −1.1 eV with PW91 and −0.91 eV with RPBE, which are systematically above the experimental value. This discrepancy between the experimental and theoretical chemical potential gives rise to a 50 K (100 K for RPBE) error bar in temperature and a factor of 10 2 (10 4 for RPBE) error bar in pressure.…”
Section: Methodsmentioning
confidence: 95%
“…Interestingly, PdO(101) on an extended (111) surface was also observed in this orientation. 147 Several other facets were observed, some of which were needed to keep the total inclination parallel to the (553) surface. These were (110), basically bunched (111) steps, and (221), 3(111) Â (111).…”
Section: à5mentioning
confidence: 99%